Pengaruh Karakteristik Perusahaan Terhadap LamanyaWaktu Penyelesaian Audit (Audit Delay)Studi empiris pada perusahaan manufaktur yang terdaftar di BEI Tahun2012-2014 - Dwiningrum, Endang; Mujiyati, M.si, Dra. Mujiyati, M.si (2016)
This research aimed to examine the influence of the characteristics of companies, which consist of company size, solvency, profit or loss of companies, the profitability and the size of the public accounting firm to audit delay. The study population is manufacturing companies listed on the stock exchanges of Indonesia in 2012-2014. purposive sampling technique used to obtain the sample size by 75 manufacturing companies with the acquisition of observational data as much as 225. Multiple regression analysis was used to test the hypothesis to explain the relationship between the variables in this research.The results showed the size of the company, solvency, profitability and profit and loss of the company have significant influence towards audit delay, while the size of the public accounting firm is no significant influence to audit delay.